Thesaurus as a tool for image indexing and retrieval in the field of cultural heritage - Zlodi, Goran (Array, 2003)
The article deals with several topics related to image indexing and retrieval in the field of cultural heritage. Structured vocabularies play an important role in improving access to cultural heritage information, and thus this article reviews methods and findings in the establishment and development of thesauri for visual collections. It also emphasises problems and possibilities for use of thesauri in a networked environment.